The beauty and the burden of being a black professor - Davis, Cheron H.; Hilton, Adriel A.; Hamrick, Ricardo; Brooks, F. Erik (Diversity in higher education ;, 2021)
It has been well chronicled that Black professors have experienced a long history of inequities and inequalities within the academic space. This volume explores the experiences, challenges and triumphs experienced by Black professors. Including personal essays written by Black professors, this volume showcases personal insights and inspirational stories from leading Black scholars across the US. It highlights and problematizes the uncomfortable truth of the lack of diversity in many higher education institutions in order to further discussions on the topic of race in academia, and to assist academics of color in preparing for their careers. Future academics will gain a sense of how to launch their careers, stay productive in research, teaching and service, and avoid the racial-related malaise that can hinder new academics of color. By presenting discussions on professional development, and emphasizing the challenges and triumphs experienced by Black professors across disciplines, this book provides advice for junior Black scholars on how to navigate academe and tackle the challenges that Black scholars often face.